A Little-Known Double-Choir Hymn Cycle from c. 1600 - Grabnar, Klemen (De musica disserenda, 2018)
An early-seventeenth-century choirbook originating from Graz surviving in Ljubljana (SI-Lnr, MS 343) contains alongside other compositions thirty-one hymns by Francesco Stivori uniquely known from this source. Stivori’s hymns form a cycle for the entire liturgical year. They follow a long tradition of polyphonic settings based on plainsong melodies, although they are set for a larger performing group than usual – eight voices distributed in two choirs. Polyphonic hymn settings in use earlier at the Graz court were not liturgically obsolete. It seems, therefore, that Stivori composed his own cycle to cater for the personal aesthetic needs of Archduke Ferdinand, who greatly favoured polychoral music.